1989
DOI: 10.1002/1097-0142(19890715)64:2<426::aid-cncr2820640215>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Stage-dependent depression of melatonin in patients with primary breast cancer. Correlation with prolactin, thyroid stimulating hormone, and steroid receptors

Abstract: Serum melatonin was determined over 24 hours in 35 patients with breast cancer with either a fresh primary tumor (n = 23) or a secondary tumor (n = 12) and in 28 patients with untreated benign breast disease (controls) having a fibroadenoma (n = 10), fibrocystic mastopathy (n = 14), or other breast diseases (n = 4). Circadian rhythms existed in all groups with acrophases at 2 a.m. A 50% depression of peak and amplitude occurred in the group of patients with primary breast cancer compared with age-matched contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(24 citation statements)
references
References 18 publications
0
22
1
1
Order By: Relevance
“…Six epidemiologic studies have reported decreased melatonin levels in patients with breast cancer (68)(69)(70)(71)(72)(73), although in each of these studies, melatonin levels were measured after diagnosis, making it uncertain whether the disease itself and/or treatment might have affected melatonin levels among the cases. At least 4 studies have measured urinary melatonin levels in women before their development of breast cancer (74)(75)(76)(77).…”
Section: Discussionmentioning
confidence: 99%
“…Six epidemiologic studies have reported decreased melatonin levels in patients with breast cancer (68)(69)(70)(71)(72)(73), although in each of these studies, melatonin levels were measured after diagnosis, making it uncertain whether the disease itself and/or treatment might have affected melatonin levels among the cases. At least 4 studies have measured urinary melatonin levels in women before their development of breast cancer (74)(75)(76)(77).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the PRL antagonist G129R was reported to cause apoptosis in breast cancer cells (8, 13). These findings, and the correlation between serum PRL and the incidence and progression of breast tumors (11,12,14), indicate that PRL has a role in human breast cancer. Stromal and adipose tissue are the major sources of estrogen in post-menopausal women, and could exert paracrine control of prolactin and prolactin receptor expression in adjacent mammary epithelial cells.…”
Section: Prolactin (Prl)mentioning
confidence: 93%
“…The third study found no relationship between melatonin level and breast cancer risk (60); however, a primary concern with that study was the use of a 24-h urine sample to assess melatonin levels, which has several concerns as described by Hrushesky and Blask (61). There is evidence that melatonin levels are decreased in patients with breast cancer, although, in each of these studies, melatonin levels were measured after diagnosis; therefore, it is uncertain whether the disease itself and/or treatment might have affected melatonin levels among the cases (62)(63)(64)(65)(66)(67). Nighttime plasma melatonin levels have been reported to be lower in women with estrogen receptor-positive breast cancer than in estrogen receptornegative breast cancer, which in turn are lower than in healthy control women, and women with the lowest peak melatonin concentrations had tumors with the highest concentrations of estrogen receptors (66).…”
Section: Cancer Epidemiol Biomarkers Prev 2008;17(12) December 2008mentioning
confidence: 99%
“…Nighttime plasma melatonin levels have been reported to be lower in women with estrogen receptor-positive breast cancer than in estrogen receptornegative breast cancer, which in turn are lower than in healthy control women, and women with the lowest peak melatonin concentrations had tumors with the highest concentrations of estrogen receptors (66). Melatonin levels have also been found to be lower in cases of primary breast cancer than in women with benign breast disease (63,67). Although these findings are consistent with the results of laboratory studies and melatonin levels are in the direction of what might be predicted, it is difficult to assess their biological relevance due to the presence of disease and its possible effect on blood melatonin levels.…”
Section: Cancer Epidemiol Biomarkers Prev 2008;17(12) December 2008mentioning
confidence: 99%